2006
DOI: 10.1007/s00442-006-0593-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecological role of reindeer summer browsing in the mountain birch (Betula pubescens ssp. czerepanovii) forests: effects on plant defense, litter decomposition, and soil nutrient cycling

Abstract: Mammalian herbivores commonly alter the concentrations of secondary compounds in plants and, by this mechanism, have indirect effects on litter decomposition and soil carbon and nutrient cycling. In northernmost Fennoscandia, the subarctic mountain birch (Betula pubescens ssp. czerepanovii) forests are important pasture for the semidomestic reindeer (Rangifer tarandus). In the summer ranges, mountain birches are intensively browsed, whereas in the winter ranges, reindeer feed on ground lichens, and the mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 53 publications
5
27
2
Order By: Relevance
“…Differences between fungal genotypes in the balancing of N-and C-metabolism might thus cause the differential mycorrhizal effects on the N supply of host plants (Table 2). In agreement with Stark et al (2007), we found a close overall relationship between the foliar concentrations of N and secondary substances (total phenolics) (Fig. 2).…”
Section: Interactions Between Host Genotype and Fungal Strainsupporting
confidence: 86%
“…Differences between fungal genotypes in the balancing of N-and C-metabolism might thus cause the differential mycorrhizal effects on the N supply of host plants (Table 2). In agreement with Stark et al (2007), we found a close overall relationship between the foliar concentrations of N and secondary substances (total phenolics) (Fig. 2).…”
Section: Interactions Between Host Genotype and Fungal Strainsupporting
confidence: 86%
“…form tannin-protein complexes, or be degraded or leached. In litter bag experiments with both spruce litter (Lorenz et al 2000) and birch litter (Stark et al 2007), tannins were lost rapidly, in some cases more than 80%, during the first year. As discussed above, in the field the concentration of total water-soluble phenolic compounds, condensed tannins and total tannins generally decreased from the litter layer to the humus layer but not as drastically as was the case with several terpenes, and the decrease was dependent on tree species (Adamczyk et al 2008b;Kanerva et al 2008).…”
Section: Occurrence Of Phenolic Compounds In Plants and Soilmentioning
confidence: 98%
“…At the Munkajaure site, which presumably was used more permanently, it is possible that the overall effect of lowintensity reindeer grazing, trampling and fertilization improved the establishment of birch (cf. Helle et al 1998, Stark et al 2007). Furthermore, just as tree species can respond individually to climatic changes (cf.…”
mentioning
confidence: 99%